Anthropometric Analysis of External Acoustic Meatus for Ergonomic Design. (December 2020) - Fan, Hao; Wang, Mengcheng; Adamson, Carisa Harris; Ren, Yihui; Chu, Jianjie; Yu, Suihuai
Ear-related wearable products have become ubiquitous and are used daily for instant communication, entertainment, hearing protection (occupational noise) and noise reduction. The proper fit of ear related wearables is imperative to their function and comfort. Prior studies have demonstrated that some anthropometric measures of the ear changes with age. However, despite this, there is a lack of relevant studies on how key dimensions of the ear, like the external acoustic meatus (EAM), change with age. Therefore, the primary purpose of this study was to define EAM measurements that are important for the ergonomic design of ear-related wearable products and explore how the EAM anthropometry changes with age.